The effects of burning forest biomass on the yield of plantain (cv. Ebang, Musa spp. AAB, false horn) after hotwater and boilingwater treatment in Southern Cameroon - Hauser, S.; Mekoa, C.; Ngo Kanga, F. (Informa UK Limited, 2012)
Plantain grown after forest slash-and-burn raises concerns due to the release of CO2 and the destruction of biodiversity. Plantain yields are presented after forest biomass was burned or retained in combination with sucker sanitation versus traditional planting. Biomass burning did not affect plant crop and total yield. Soil chemical properties were weakly positively affected by burning. Sucker sanitation increased total yield at one site from 6.2 to 9.7 Mg ha71 (p ¼ 0.015), without effects on root health. In the second site, sucker sanitation had no effect on fresh bunch yield (mean 8.59 Mg ha71), yet significantly improved root health parameters. Thus, at the first site, sucker sanitation elicited a positive response via a mechanism different from nematode control. At the second site, by contrast, nematode control was not the most important factor in yield formation. These data do not support the notion that retaining biomass increases plantain production. Other factors related to labor requirements and later weed infestation are probably more important in farmers’ decision making on biomass management.